POTENSI SUMBERDAYA AIR DAS SERAYU - Purnama, Setyawan (BPPT)
Serayu River Basin is one of critical river basin in Java. This problems become seriously because the river basin cover wide area, that almost cover most of the south of Central Java Province. This research is aimed to calculate and analyse the resources potency of rainfall, river, groundwater and springs. Rainfall potency is calculated by isohyetal method, river potency is determined base onhydograph dan water level data. Groundwater and springs is determined qualitatifly base on Hydrogeological Map, whereas quantitatifly is calculated by meteorogical method base on water balance concept in river basin. As a result, show that the average rainfall in Serayu River Basin is 3,577 m3/year, whereasthe rainfall potency is 13,481.00 x 106 m3/year. The average of monthly maximum discharge in Serayu is 60 m3/second, with monthly minimum discharge 11 m3/second. Meteorologically, groundwater storage in Serayu River Basin is 105,981,890 m3/year. Beside that, in Serayu River Basin also have 93 springs, that is 10 springs with discharge more than 500 litre/second, 15 springs with discharge 50-100 litre/second, 20 springs with discharge 10-50 litre/second and 24 springs with discharge less than 10 litre/second.Keywords : Water resources potency, Serayu River Basin